e-Leadership: Pelatihan Kepemimpinan Era Digital bagi Pemerintah Pekon Suka Maju Kecamatan Ngaras Kabupaten Pesisir Barat - Nanda Syukerti; Adli Adli; Intan Putri; Dendi Dendi; Insan Maulana; Rizki Eriyansyah; Hariyadi Hariyadi (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2023)
Technological developments are getting faster and faster, including evolutions that occur in the field of technology and internet innovation which have an impact on changes in the industrial era 4.0. communication related to interaction also changes. For example, the internet is used not only to find information, but is also used to assist village officials in managing village data and to facilitate communication between Suka Maju village officials. This program aims to hone skills in using communication technology for Pekon devices. This activity was carried out in the form of training involving lecturers, students and all village officials. The main target of this activity is Pekon Suka Maju from several hamlets. The first step taken was socialization of the activity plan by distributing brochures and pamphlets at the Pekon hall. then the e-Leadership training and mentoring process so that it becomes a pekon tool that is proficient in using communication technology, through google drive, google doc, google meet, google sheets and others. This program was implemented well and the Pekon Suka Maju officials were able to apply this communication technology in village data management. So that village device activities are more effective and efficient in achieving village goals and sustainability in the future.